Decompositions of direct products of groups - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We propose a new method for the decomposition of direct products of groups into U subsets. By using this method, we prove the following generalization of the Comfort-van Mill theorem: An arbitrary nondiscrete topological Abelian group with a finite number of second-order elements can be decomposed into a countable number of dense subsets.